The Influence of Work Environment and Communication on Organizational Commitment with Teamwork as an Intervening Variable at the Medan Religious Training Center - Rio Yudha Syahputra; Mesra B (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research aims to see the influence of the Work Environment and Communication on Organizational Commitment with Teamwork as an intervening variable at the Medan Religious Education and Training Center. This research uses associative quantitative research and primary data sources. This research was conducted at the Medan religious training center, the population in this study was 60 employees and used a saturated sampling technique to calculate the sample. Data were collected by distributing questionnaires, this research model uses analytical tools and the research measuring tool uses smart PLS version 3. The results of this research are as follows: Teamwork has a positive and significant effect on Organizational Commitment with an original sample value of 0.326 and P values 0.041. Communication has a positive and significant effect on Teamwork with an original sample value of 0.227 and a p value of 0.026. Communication has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.134 and a P value of 0.422. Work Environment has a positive and significant effect on Teamwork with an original sample value of 0.597 and a p value of 0.000. Work Environment has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.254 and a p value of 0.175. Communication has a positive and insignificant effect on Organizational Commitment through Teamwork with an original sample value of 0.074 and a p value of 0.187. Work Environment has a positive and insignificant effect on Organizational Commitment through Teamwork with an original sample value of 0.195 and a p value of 0.053.